Faktor-faktor yang Mempengaruhi struktur Modal - Kiki Nurhalimah; Yuli Chomsatu (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
Abstract: : Capital structure is a complex financial decision because it is related to other financial decision variables. This research aims to find out the factors that influence the capital structure. The population in this research is pharmaceutical companies that are listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sample was chosen from the purposive sampling method and obtained a sample of 8 pharmaceutical companies. The data source is secondary data from the website (www.idx.co.id). This research uses multiple linear regression analysis with the help of SPSS version 21. The results of this study indicate that liquidity, business risk, company growth influence the company's capital structure. While profitability, company size, sales growth and asset structure have no effect on capital structure. The results of this research are expected to be a material consideration for company management in deciding policies on capital structure and providing information on users of financial statements for consideration of investment decisions.